Patients with IDH1 wild type anaplastic astrocytomas exhibit worse prognosis than IDH1-mutated glioblastomas, and IDH1 mutation status accounts for the unfavorable prognostic effect of higher age: implications for classification of gliomas - Hartmann, Christian; Hentschel, Bettina; Wick, Wolfgang; Capper, David; Felsberg, Jörg; Simon, Matthias; Westphal, Manfred; Schackert, Gabriele; Meyermann, Richard; Pietsch, Torsten; Reifenberger, Guido; Weller, Michael; et al. (Acta neuropathologica, 2010)
WHO grading of human brain tumors extends beyond a strictly histological grading system by providing a basis predictive for the clinical behavior of the respective neoplasm. For example, patients with glioblastoma WHO grade IV usually show a less favorable clinical course and receive more aggressive first-line treatment than patients with anaplastic astrocytoma WHO grade III. Here we provide evidence that the IDH1 status is more prognostic for overall survival than standard histological criteria that differentiate high-grade astrocytomas. We sequenced the isocitrate dehydrogenase 1 gene (IDH1) at codon 132 in 382 patients with anaplastic astrocytoma and glioblastoma from the NOA-04 trial and from a prospective translational cohort study of the German Glioma Network. Patients with anaplastic astrocytomas carried IDH1 mutations in 60%, and patients with glioblastomas in 7.2%. IDH1 was the most prominent single prognostic factor (RR 2.7; 95% CI 1.6-4.5) followed by age, diagnosis and MGMT. The sequence from more favorable to poorer outcome was (1) anaplastic astrocytoma with IDH1 mutation, (2) glioblastoma with IDH1 mutation, (3) anaplastic astrocytoma without IDH1 mutation and (4) glioblastoma without IDH1 mutation (p < 0.0001). In this combined set of anaplastic astrocytomas and glioblastomas both, IDH1 mutation and IDH1 expression status were of greater prognostic relevance than histological diagnosis according to the current WHO classification system. Our data indicate that much of the prognostic significance of patient age is due to the predominant occurrence of IDH1 mutations in younger patients. Immunohistochemistry using a mutation-specific antibody recognizing the R132H mutation yielded similar results. We propose to complement the current WHO classification and grading of high-grade astrocytic gliomas by the IDH1 mutation status and to use this combined histological and molecular classification in future clinical trials.